Bio-Inspired New Hydraulic Actuator Imitating the Human Muscles for Mobile Robots - Bai, Xiangjuan; Xue, Yong; Xu, Yuze; Shang, Jianzhong; Luo, Zirong; Yang, Junhong (Frontiers in Bioengineering and Biotechnology, 2022)
Limited load capacity is the bottleneck for the practical application of mobile multi-joint legged robots. And improving the efficiency of the drive system is a key factor in improving the load capacity. To improve the efficiency of mobile robots, in this paper, a new kind of actuator that imitates the driving mechanism of human muscles is innovatively designed and validated through experiments. The proposed actuator consists of a single power source and multiple plunger pistons, and imitates the configuration of a human muscle, to improve the efficiency and load capacities. The design proposed here represents a new class of driving methods. The actuator selects the most appropriate combination of the effective areas of plunger pistons like the human muscles, to ensure that the maximal output force aligns with the load force. To validate that the new actuator can improve the efficiency of hydraulic systems of mobile robots, a robotic arm incorporating a prototype of the new actuator was designed. The proposed system was validated through a series of experiments. The experiments show that the bionic actuator can adjust the flow rate of the system input by adjusting the number and size of the motion units involved in the work, and with the change in load force, it changes the output force by recruiting different motion units, which indicates good controllability. The results reported herein reveal that the application of bionics to the design of robotic actuator can significantly improve the efficiency and overall performance of the robots, and this biomimetic approach can be applied to a variety of robots.